2016
DOI: 10.1016/j.hemonc.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of gonadal hormones in Egyptian female children with sickle cell anemia in correlation with iron overload

Abstract: Female patients with SCA with iron overload may have gonadal hormone deficiency with significant negative correlations between gonadal hormones including FSH, LH, estrogen, and serum ferritin. Recommendations include regular iron chelation for prevention of irreversible damage of the ovaries and attaining normal sexual maturation, and regular follow up for females with SCA with assessment of puberty as they are more vulnerable to develop hypogonadism and may require hormonal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Another important reason for infertility is hypogonadotrophic hypogonadism due to deposition of iron in the hypothalamo-pituitary axis because of multiple blood transfusions and iron overload. A single-center study in Egypt demonstrated that adolescents with SCD and excessive iron stores have significantly lower levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), and estrogen when compared to those without excessive iron stores 8…”
Section: Methodsmentioning
confidence: 99%
“…Another important reason for infertility is hypogonadotrophic hypogonadism due to deposition of iron in the hypothalamo-pituitary axis because of multiple blood transfusions and iron overload. A single-center study in Egypt demonstrated that adolescents with SCD and excessive iron stores have significantly lower levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), and estrogen when compared to those without excessive iron stores 8…”
Section: Methodsmentioning
confidence: 99%
“…However, AMH levels were inversely correlated with non‐transferrin‐bound iron and labile plasma iron levels, and were lower in women over 30 years old, suggesting that iron has a long‐term gonadotoxic effect . Even with iron level normalization, this process is irreversible …”
Section: Benign Hematological Diseasesmentioning
confidence: 99%
“…15 Even with iron level normalization, this process is irreversible. 16 Finally, ovarian damage and inflammatory mediators during ischemia in vaso-occlusive crises have been proposed to be among the disrupting factors that may also explain premature ovarian aging in these women. 15 Hydroxyurea is a standard long-term treatment administered to patients with sickle cell disease or myeloproliferative diseases.…”
Section: B Eni G N Hematolog I C Al D Is E a S E Smentioning
confidence: 99%
“…Endocrine disorders appear to be related to vaso-occlusive and ischemic events, rather than iron overload resulting from frequent transfusion [9]. According to the literature, the prevalence of endocrine and metabolic disorders in children with SCD varies in different populations depending on the literacy rate, socioeconomic status, and access to appropriate treatment [7, 9, 10, 12]. In children with HbSS, the treatment with HU has been demonstrated to allow growth rates similar to patients with HbSβ + or healthy controls [13].…”
Section: Introductionmentioning
confidence: 99%